Carboxylesterase 1 (Ces1): from monocyte marker to major player. Issue 2 (22nd December 2010) - Markey, Geraldine M
Abstract : There are few, if any, enzymes that have been studied by, and have importance in, so many and varied disciplines as has monocyte esterase/Ces 1. In this review its involvement in the fields of histochemistry, haematology, toxicology, pharmacology, therapeutics, and tumour cell killing, immune surveillance and malignant disease, is briefly described.